2012
DOI: 10.1039/c2cp22325b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the solubility of triamino-trinitrobenzene in hydrous tetramethylammonium fluoride: a first principles molecular dynamics simulation study

Abstract: With the aim to understand the relatively high solubility of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB), an important energetic material with a high degree of inter- and intra-molecular hydrogen bonding, in fluoride anion containing ionic liquids (ILs), first principles molecular dynamics simulations in the isobaric-isothermal ensemble were carried out for a system using hydrous tetramethylammonium fluoride as the prototypical solvent. Simulations initiated from both molecular TATB and its Meisenheimer comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It crystallizes in a triclinic cell of space group P1 1,2 and exhibits very anisotropic thermo-mechanical and chemical behavior 3,4 due to the arrangement in layers of the two C 6 H 6 N 6 O 6 molecules (see Figure 1). Such anisotropic properties are also the consequences of the directional interactions within the molecular crystal, which give to the strength a high sensitivity toward the direction of loading (up to a factor 20 for shear), as indicated by computations of the second order stiffness tensor C. [5][6][7] Experiments have pointed out that TATB grown single crystals are noticeably defective, [8][9][10][11][12] with the presence of porosities, twinned structures, etc. Until recently TATB single crystals of size compatible with standardized mechanical experiments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It crystallizes in a triclinic cell of space group P1 1,2 and exhibits very anisotropic thermo-mechanical and chemical behavior 3,4 due to the arrangement in layers of the two C 6 H 6 N 6 O 6 molecules (see Figure 1). Such anisotropic properties are also the consequences of the directional interactions within the molecular crystal, which give to the strength a high sensitivity toward the direction of loading (up to a factor 20 for shear), as indicated by computations of the second order stiffness tensor C. [5][6][7] Experiments have pointed out that TATB grown single crystals are noticeably defective, [8][9][10][11][12] with the presence of porosities, twinned structures, etc. Until recently TATB single crystals of size compatible with standardized mechanical experiments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An increased solubility of the hard-to-dissolve molecular crystal, 1,3,5-triamino-2,4,6-trinitrobenzene, was observed in hydrous ionic liquid, tetramethylammonium fluoride, as compared to that in other solvents. 7 A phenomenal increase in solubility of nucleobases was found in 1-ethyl-3-methylimidazolium acetate, [Emim][Ac] and 1-butyl-3-methylimidazolium acetate, and [Bmim][Ac] relative to water. 8,9 In these systems, the hydrogen bonding between the acetate anion of the ionic liquid and amine groups of nucleobase is the primary factor of dissolution mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mathew et al 6 and Kroonblawd et al 7 studied through molecular dynamics (MD) simulations its elastic− plastic response under displacement-controlled nanoindenta- tions and under shock. They reported that some studies 8 have suggested the existence of high defect density in grown crystals of TATB and subtle structural phase transitions under hydrostatic compression. The generalized stacking fault energies within the two glide planes have been computed 5 using all-atom simulations with a classical force field and suggested that easy dislocation glide could be present in TATB.…”
Section: Introductionmentioning
confidence: 99%